2013
DOI: 10.3389/fpls.2013.00199
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between strigolactones and other plant hormones in the regulation of plant development

Abstract: Plant hormones are small molecules derived from various metabolic pathways and are important regulators of plant development. The most recently discovered phytohormone class comprises the carotenoid-derived strigolactones (SLs). For a long time these compounds were only known to be secreted into the rhizosphere where they act as signaling compounds, but now we know they are also active as endogenous plant hormones and they have been in the spotlight ever since. The initial discovery that SLs are involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 154 publications
(284 reference statements)
2
89
0
1
Order By: Relevance
“…9 Strigolactones, the major class of germination stimulants, 14 are derived from carotenoids through two subsequent enzymatic cleavage steps performed by the carotenoid cleaving dioxygenases CCD7 and CCD8. [29][30][31][32] To date, the impact of virus-infected host plant on parasitism by Phelipanche has not been reported, therefore our study focused on carotenoid content in CMV-infected tobacco roots and its effect on the development of the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…9 Strigolactones, the major class of germination stimulants, 14 are derived from carotenoids through two subsequent enzymatic cleavage steps performed by the carotenoid cleaving dioxygenases CCD7 and CCD8. [29][30][31][32] To date, the impact of virus-infected host plant on parasitism by Phelipanche has not been reported, therefore our study focused on carotenoid content in CMV-infected tobacco roots and its effect on the development of the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…changes in leaf venation and secondary growth of transgenic A. thaliana At_GFP-SAD1. [8][9][10] Since we did not detect these additional phenotypes, we speculate that SAD1 manipulates bud outgrowth by hormone-independent regulatory pathways. Detailed evaluation of At_GFP-SAD1 plant development revealed that expression of GFP-SAD1 induces abortion of siliques at early stages of silique development in A. thaliana (Fig.…”
mentioning
confidence: 66%
“…7 Hormones like auxin and strigolactones are main players in control of bud outgrowth. 8 If SAD1 modulated branching by interfering with these hormones, we would expect to observe additional phenotypes, i.e. changes in leaf venation and secondary growth of transgenic A. thaliana At_GFP-SAD1.…”
mentioning
confidence: 99%
“…Two developmental stages, the formation of axillary meristems and the subsequent axillary bud outgrowth, are involved in shoot development (Shimizu-Sato and Mori, 2001), and many researches have tried to elucidate the mechanisms of the two stages. It has been demonstrated that three phytohormones, auxin, cytokinin, and strigolactone, participate in the regulation of axillary bud outgrowth, while auxin and strigolactone act as inhibiters and cytokinin acts as a promoter (Cheng et al, 2013). The mechanism underlying axillary meristem initiation is unclear, despite the fact that a set of pathway transcription factors have been identified from branching-deficient mutants, including: 1) the NAC domain protein CUP-SHAPED COTYLEDON3 (CUC3) from Arabidopsis (Vroemen et al, 2003;Hibara et al, 2006); 2) the GRAS domain protein LATERAL SUPPRESSOR (LAS) from Arabidopsis (Greb et al, 2003), and its homolog Ls from tomato (Schumacher et al, 1999), as well as MONOCULM1 (MOC1) from rice (Li et al, 2003); 3) R2R3 MYBs LATERAL ORGAN FUSION1/2 (LOF1/2) (Lee et al, 2009) and REGULATOR OF AXILLARY MERISTEMS (RAX1/2/3) (Keller et al, 2006;Müller et al, 2006) from Arabidopsis, and their respective homologs TRIFOLIATE (Tf) (Naza et al, 2013) and BLIND (Bl) (Schmitz et al, 2002) from tomato; 4) the bHLH protein REGULATOR OF AXILLARY MERISTEM FORMATION (ROX) from Arabidopsis (Yang et al, 2012), and its orthologs LAX PANICLE1 (LAX1) from rice (Komatsu et al, 2001(Komatsu et al, , 2003 and BARREN STALK1 (BA1) from maize (Gallavotti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%